Growing Teratoma Syndrome: A case report - Elif Sitre Koç; Öykü Beyaz (Van Tıp Dergisi, 2021)
Germ cell tumors of the testis comprosing of seminomas, or non-seminomatous germ cell tumors are the most common solid neoplasms in young men. There are rare cases where seminoma and non-seminomatous cells are seen together. Non-seminomatous germ cell tumors which have generally good prognosis may feature with growing masses, despite chemotherapy treatment and consequent diminishing or normal tumor markers. These cases are called Growing Teratoma Syndrome (GTS). Growing Teratoma Syndrome is diagnosed with: (i) normalization of tumor markers (AFP and / or hCG) that have been elevated before chemotherapy, (ii) increased tumor volume during or after chemotherapy, and (iii) biopsy result consistent with mature teratoma. In the management of GTS, the early and complete surgical removal of the tumor constitutes the main approach. Early diagnosis and correct intervention GTS cases have a very good prognosis. Herein, we report a patient diagnosed with GTS after two courses of chemotherapy.